A novel approach to sampled-data filter design for piecewise-affine systems. (November 2019) - Wei, Yanling; Qiu, Jianbin; Karimi, Hamid Reza
Abstract: This paper is concerned with the problem of sampled-data piecewise-affine (PWA) filter design of PWA systems via continuous piecewise Lyapunov functionals. Especially, an input delay scheme is initially introduced to characterize the sample-and-hold behavior with a time-varying delayed measurement output. Then, an improved ℋ ∞ performance analysis criterion is presented for the filtering error systems, which is achieved by constructing a novel continuous piecewise Lyapunov–Krasovskii functional and an extended integral inequality. Furthermore, with a linearization procedure, the full-order and reduced-order PWA filter synthesis is developed in a unified framework. Simulation studies are conducted to demonstrate the efficacy and less conservativeness of the proposed approach.